Assessing Cochlear Length Using Cone Beam Computed Tomography in Adults With Cochlear Implants. Issue 9 (October 2018) - Alnafjan, Fadwa F.; Allan, Stuart M.; McMahon, Catherine M.; da Cruz, Melville J.
Abstract : N/A: Developing a clinically viable technique for measuring cochlear length could enhance future electrode design of cochlear implants and surgical skills to improve clinical outcomes. While computed tomography (CT) has been used, metal artifact and the exposure to higher levels of radiation limits its use. More recently, cone beam CT (CBCT) has been used to assess the integrity of the implant array in situ, exposing implantees to lower levels of radiation while retaining image quality. The current study aims to develop a technique for measuring cochlear length in implanted adults, using CBCT images combined with known dimensions of implant arrays and lengths of cochlear structures from cadaveric human temporal bones. Study Design: One hundred CBCT temporal bone images of ears implanted with Cochlear straight or perimodiolar arrays were reviewed by two independent examiners. Results: Outer-wall length, based on the position of the straight array within the cochlea and the reported average length of the organ of Corti, was 27.44 to 35.91 mm (mean = 32.24 mm). Inner-wall length, based on the position of the perimodiolar array and the reported average length of the spiral ganglion, ranged from 17.8 to 22.24 mm (mean = 19.43 mm). Conclusion: A novel method for calculating outer- and inner-wall cochlear length using CBCT images has been developed which is feasible in clinical settings.